The criative capital and the guidelines for the education and development of young in Brazil - Maranhão, Andreia Pagani (Revista Hipótese, 2018)
In this essay, we have tried to lay out how multilateral norms for the education of Young in the country are laid and developed. We start of the Reading of the strategic guidelines of de World Bank and brazilian norms. We emphasize that as educational policies lose specificity, becoming in integrated part of the work and economy as objetcts of the recomposition of productive capital and hegemonization of the way of life, There is also a tendency to profissionalize precariously of the students as sign of the reconstruction of the working class.